Organizational and economic mechanisms for improving water consumption management in economic sectors based on innovative technologies - Karimov Anvarjon Mukumjonovich (THE INNOVATION ECONOMY, 2026)
This article substantiates the need to introduce innovative technologies to improve the efficiency of water consumption in economic sectors. The shortcomings of the existing management system are analyzed, and organizational-economic mechanisms for their elimination are proposed. It presents ways to optimize water consumption based on digitalization, IoT, and artificial intelligence